![P=f(t)=P(1-0.039)^t](https://img.qammunity.org/2023/formulas/mathematics/college/9cv2djailjlc4oonjyqmcj4rdvfa5o908o.png)
Step-by-step explanation
Step 1
let
![P=f(t)](https://img.qammunity.org/2023/formulas/mathematics/college/b8db849q0yvlvvnjjgwv8okpbbo4dfj9cp.png)
where P represent the population, and t represents the time in years
so,
when t=0, P=2070
![\begin{gathered} P=f(t) \\ 2070=f(0) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ocqm5k9oq5iz32kcv4dbc4v77or75qgb9m.png)
Step 2
if the population decrease 3.9% every year,in decimal form
![\begin{gathered} \text{3}.9\text{ =3.9/100= 0.039} \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6ye1w5hx1lhikiegivfzlmgz992x99x3n4.png)
so,after 1 year the population is
![\begin{gathered} P_1=P(1-0.039)\rightarrow Eq1 \\ P_1=P(0.961) \\ P_1=2070(0.961) \\ P_1=1989.27 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/tgcshz7wvwenmwgn0rjcsxzskk05l045yv.png)
now, after the 2 years
![\begin{gathered} P_2=P_1(1-0.039)=P(1-0.039)(1-0.039)=P(1-0.039)^2 \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/51ik3rb0zrl8r3wfdxykju6ebv2laczpg5.png)
now, after 3 years
![P_3=P_2(1-0.039)=P(1-0.039)(1-0.039)(1-0.39==P(1-0.039)^3](https://img.qammunity.org/2023/formulas/mathematics/college/r74o6kdbdvwq8gau6cowi08x28v7ux39yl.png)
now, we can see the function
![\begin{gathered} P(1-0.039)^t\rightarrow P_f=P(1-0.039)^t \\ f(t)=P(1-0.039)^t \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/2qxwl4w76dos4g1xm8jvr2a19662be8u1r.png)
I hope this helps you